SCIENTIFIC SUBSTANTIATION OF THE RELEVANCE OF THE PROBLEM OF DEVELOPING SPEED OF MOVEMENT AND ACCURACY OF SHOTS IN TABLE TENNIS FROM A VERY EARLY AGE (Scientific journal of the Fergana State University, 2024)
The article reviews and analyzes various literary sources on table tennis in order to determine the relevance of the problem of increasing and maintaining stability of the implementation and precision-targeted game actions in table tennis to the effects of multidirectional angular accelerations with an emphasis on body rotation.